AB0575 THE ROLE OF LONG-TERM AND INTENSIVE IV ILOPROST TREATMENT IN REDUCTION OF PULMONARY ARTERY PRESSURE AND PRO-BRAIN NATRIURETIC PEPTIDE (PBNP) IN SCLERODERMA PATIENTS. (13th June 2020) - Foti, R.; Visalli, E.; Amato, G.; Benenati, A.; Bellofiore, S.; Mule', M.; DI Gangi, M.
Abstract : Background: Systemic sclerosis (SSc) is a chronic immune-mediated connective tissue disease with heterogeneous organ involvement that reduces the life expectancy of this patients. In particular cardiopulmonary manifestations, such as pulmonary arterial hypertension (PAH), are currently the primary cause of death and stabilizing this condiction may represent an important therapeutic goal (1, 2). An increased NT-proBNP is predictors of PAH in SSc and use this markers should result in improved PAH risk stratification (3)Some studies have suggested the role of intravenous iloprost in preventing the incidence of most severe vascular complications in long term treated patients (4). Objectives: The aim of our study is to evaluate the evolution of the disease, with particular focus on cardiopulmonary function, in a group of consecutive patients chronically treated with iloprost at the Rheumatology Unit of Catania Hospital, Italy, from 2006 to 2019. Methods: 68 SSc patients (58F, 52.88 ± 12.6 years). At baseline, 67.6%, 25% and 5.9% had a limited, diffuse and early scleroderma type respectively and 20, 6% had interstitial lung disease. The follow-up period of the study was of 9.9 ± 2.9 years. Iloprost was administered with a regimen of 6 infusions per month (6 hours/day, 0.5-2.0 ng/kg/min) to treat secondary Raynaud's phenomenon (RP), diagnosed at an average age of 46.6 ± 13.7 years. We evaluated: skin score (SS), systolic pulmonary arterial pressure (PAPs), plane tricuspid annular systolic excursion (TAPSE), lung diffusing capacity of carbon monoxide (DLCO), forced vital capacity (FVC), alveolar volume (VA), DLCO/VA, pro-brain natriuretic peptide (pBNP), and NYHA class.We analyzed the patients as a whole group (68 subjects), as a group who continued the treatment (57 subjects) and as a group who stopped the treatment during the follow-up (11 patients). Results: After the long follow up period in the study (almost 10 years) in the whole group of patients, PAPs and pBNP showed statistically significant improvement from baseline (30.91 ± 6.4 vs 27.36 ± 7.1 and 97.20 ± 69.3 vs 66.65 ± 44.3 respectively, p < 0.0001 for both) while the other parameters showed no significant changes: SS (4.70 ± 5.3 vs 3.86 ± 4.2 mm), TAPSE (22.07 ± 2.4 vs 22.06 ± 3.8 mm), DLCO (83.68 ± 13.5 vs 77.70 ± 14.6 mmol/kPa.min), FVC (107.09 ± 14.5 vs 107.72 ± 18.7 liters), VA (91.12 ± 13 vs 90.30 ± 14.4 liters), DLCO/VA (88.48 ± 13.5 vs 89.5 ± 16.3) and NYHA class (1.0 ± 0.0 vs 1.0 ± 0.0). A subgroup analysis indicated a significant improvement in addition to PAPs and pBNP also for skin score for 57 patients who continued the treatment (5.09 ± 5.7 vs 3.30± 4.2, p < 0.0001) and a significant worsening of this parameter as early as the first year of suspension (p <0.05 year 1, p<0.01 year 2 and 3) in 11 patients who stopped the treatment. Conclusion: Cardiac involvement is recognised as a poor prognostic factor among systemic sclerosis (SSc) patients, significantly to mortality and N-TproBNP peptide may represent a surrogate marker for cardiac involvement in SSc, selectively identifying patients with severe impairment of cardiac function. Our intensive (6 infusions/month) and chronic regimen of iv iloprost administration seems improve the long-term evolution of disease in SSc patients, as suggested by the improvement of cardiopulmonary parameters and the significant improvement of SS. References: [1]Rheumatology 51, 1027-36 2) Best Pract Res Clin Rheumatol.32, 223-240 3) Arthritis Rheum. 2008 58, 284-9 4) Rheumatol Int 2012;32:1933-8. Disclosure of Interests: Rosario Foti Consultant of: lilly, sanofi, MSD, Janssen, Abbvie, BMS, celgene, roche, Speakers bureau: lilly, sanofi, MSD, Janssen, Abbvie, BMS, celgene, roche, elisa visalli Consultant of: lilly, sanofi, MSD, Janssen, Abbvie, BMS, celgene, roche, Speakers bureau: lilly, sanofi, MSD, Janssen, Abbvie, BMS, celgene, roche, Giorgio Amato: None declared, Alessia Benenati: None declared, Salvatore Bellofiore: None declared, Massimiliano Mule': None declared, Marcella Di Gangi: None declared